Plasmid-determined resistance to fosfomycin in Serratia marcescens. - Mendoza, C (1980)
Multiple-antibiotic-resistant strains of Serratia marcescens isolated from hospitalized patients were examined for their ability to transfer antibiotic resistance to Escherichia coli by conjugation. Two different patterns of linked transferable resistance were found among the transconjugants. The first comprised resistance to carbenicillin, streptomycin, and fosfomycin; the second, and more common, pattern included resistance to carbenicillin, streptomycin, kanamycin, gentamicin, tetracycline, chloramphenicol, sulfonamide, and fosfomycin. The two types of transconjugant strains carried a single plasmid of either 57 or 97 megadaltons in size. Both of these plasmids are present in parental S. marcescens strains resistant to fosfomycin. The 57-megadalton plasmid was transformed into E. coli.